A Facile and Versatile “Click” Approach Toward Multifunctional Ionic Metal–organic Frameworks for Efficient Conversion of CO2 - Zhou, Li‐Jiao; Sun, Wei; Yang, Ning‐Ning; Li, Peng; Gong, Teng; Sun, Weng‐Jie; Sui, Qi; Gao, En‐Qing (ChemSusChem, 2019)
Ionic metal–organic frameworks (IMOFs) that integrate synergistic Lewis‐acid sites (intrinsic metal centers of the frameworks) and nucleophilic anions (halides encapsulated within pores) are intriguing platforms for the design of fully heterogeneous catalytic systems for cycloaddition of CO2 to epoxides. A new, facile and versatile synthetic approach has been used to fabricate triazolium‐based IMOFs for the first time. The approach makes use of azide–alkyne click chemistry and subsequent N‐alkylation to post‐synthetically create a cationic triazolium ring and introduce exchangeable counteranions at the same time. The IMOFs are efficient and recyclable heterogeneous catalysts for CO2 conversion under mild and cocatalyst‐free conditions. In particular, the click‐accessible triazolium ring provides a handle to incorporate further functionality. The MIL‐101‐tzmOH‐Br catalyst, which integrates hydrogen‐bonding hydroxy groups besides metal centers and bromide anions, shows superior catalytic performance under mild conditions. Click here to convert CO2! An ionic metal–organic framework (IMOF) bearing a CrIII center at the node, a hydroxy group grafted to the cationic linker and a bromide anion encapsulated within the pore is fabricated by facile azide–alkyne click chemistry. The multifunctional IMOF presents superior heterogeneous catalytic activity for cycloaddition of CO2 to epoxides under mild and cocatalyst‐free conditions.